Solution for What is 65 percent of 60:

65 percent *60 =

(65:100)*60 =

(65*60):100 =

3900:100 = 39

Now we have: 65 percent of 60 = 39

Question: What is 65 percent of 60?

Percentage solution with steps:

Step 1: Our output value is 60.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{60}={100\%}.

Step 4: Similarly, {x}={65\%}.

Step 5: This results in a pair of simple equations:

{60}={100\%}(1).

{x}={65\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{60}{x}=\frac{100\%}{65\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{60}=\frac{65}{100}

\Rightarrow{x} = {39}

Therefore, {65\%} of {60} is {39}

Solution for What is 60 percent of 65:

60 percent *65 =

(60:100)*65 =

(60*65):100 =

3900:100 = 39

Now we have: 60 percent of 65 = 39

Question: What is 60 percent of 65?

Percentage solution with steps:

Step 1: Our output value is 65.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{65}={100\%}.

Step 4: Similarly, {x}={60\%}.

Step 5: This results in a pair of simple equations:

{65}={100\%}(1).

{x}={60\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{65}{x}=\frac{100\%}{60\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{65}=\frac{60}{100}

\Rightarrow{x} = {39}

Therefore, {60\%} of {65} is {39}